Peran Keluarga terhadap Pendidikan Agama Bagi Anak dalam Perspektif Islam - Isti Mahfuzhah; Ajat Rukajat; Khalid Ramdhani (AS-SABIQUN, 2022)
Parents are people who are mandated by Allah SWT to guide children with full responsibility and love in the family environment. To be able to improve the quality of the nation, education development is needed. Education seeks to educate people to have knowledge and skills as well as faith and piety to Allah SWT. This writing aims to determine the role of the family in Islamic religious education for children. The method used is descriptive qualitative method. The process of data collection using literature study. The results of this study discuss the role of the family in Islamic religious education for children by instilling religion as a motivation for life and life as a means of self-control. And understand that religion is very important in creating a complete human being. The conclusion of this study is that the role of parents in religious education for children is very important to instill a child's love for religion, obedience to Allah SWT and His Messenger. provide provisions for living the life of this world and the hereafter. And foster discipline, love of religion and piety.